2013
DOI: 10.1016/j.wear.2012.12.026
|View full text |Cite
|
Sign up to set email alerts
|

A study on PDC drill bits quality

Abstract: The quality of innovating PDC bits materials needs to be determined with accuracy by measuring cutting efficiency and wear rate, both related to the overall mechanical properties. Therefore, a lathe-type test device was used to abrade specific samples. Post-experiment analyzes are based on models establishing coupled relations between cutting and friction stresses related to the drag bits excavation mechanism. These models are implemented in order to evaluate cutting efficiency and to estimate wear of the diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 16 publications
1
43
0
1
Order By: Relevance
“…where F t is the friction force, v ir rt is the irreversible part of the relative tangential velocity, and 0 ≤ χ ≤ 1 is the part of the friction work converted to heat. Heat generated at the contact point is absorbed by the contacting particles (37) If the particles are of the same materials, it is assumed that the heat is absorbed equally by the particles:…”
Section: Thermomechanical Contactmentioning
confidence: 99%
“…where F t is the friction force, v ir rt is the irreversible part of the relative tangential velocity, and 0 ≤ χ ≤ 1 is the part of the friction work converted to heat. Heat generated at the contact point is absorbed by the contacting particles (37) If the particles are of the same materials, it is assumed that the heat is absorbed equally by the particles:…”
Section: Thermomechanical Contactmentioning
confidence: 99%
“…2c presents the Co concentrates at the gaps among the diamond grains as well as the interface between PCD layer and WC-Co substrate. The Co phase in PCD layer is due to the infiltration of the Co from the WC-Co substrate during sintering [8]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…2c. The previous references [8,17] have indicated that W, with very low quantity, comes from thermal diffusion and infiltration during sintering process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also reported that fine tungsten carbide grain size and a low level of cobalt content lead to higher hardness and good wear resistance, whereas coarse particles and high cobalt content produce low hardness and high wear rate (Mori, et al, 2003;Ndlovu, 2009). Yahiaoui, et al (2013) stated that the grain size and the content of cobalt are the most significant parameters of PDC cutters as high wear rate is associated with large particle size. Bellin, et al (2010b) reported that the increasing the cobalt content in the diamond layer and the substrate will increase the fracture toughness, whereas the wear resistance increases with lower cobalt content.…”
Section: B Microstructural Properties and The Cobalt Content Of Pdc mentioning
confidence: 99%